Penoscrotal elephantiasis: Case report - Anna Jędrowiak; Magdalena Oszukowska; Anna Żuchowska; Katarzyna Tabara; Anna Szewczyk; Mirosława Kuchciak-Brancewicz; Andrzej Kaszuba (Our Dermatology Online, 2016)
Genital elephantiasis is characterized by massive growth of genitals as a result of chronic lymphedema caused by numerous infectious and noninfectiuos triggers. In most cases it occurs in filarial endemic zones and is rarely encountered in developed nations. Herein, we report a case of 33-year-old previously healthy patient who presented with rapid penoscrostal enlargement and systemic signs due to probable streptococcal contagion after a surgical treatment of phimosis subsequently complicated with chronic penoscrotal lymphedema. Genital elephantiasis is usually irreversible with systemic therapy alone and frequently requires surgical procedures following the acute stage of the disease